Micro Insurance Matters in Latin America - Goldberg, Mike; Ramanathan, C.S. (World Bank, Washington, DC, 2012)
This note discusses the rapidly evolving issue of micro insurance in Latin America and how microfinance institutions (MFIs), insurance companies and donors can respond to its challenges. This note is part of a series summarizing the Department of International Development-Latin American Markets and International Trade Program (DFID-LAMIT) eight-part distance learning program with South American microfinance networks and government officials. This note addresses three critical questions about micro insurance in Latin America. 1) What is micro insurance? 2) Is micro insurance a very useful way for low income households to manage their risks? 3) What are the challenges for expanded coverage of commercial micro insurance in Latin America, and what can governments, donors and investors do to help?